Internal IT Audit Engagement : IT Operations, including implementation of JIRA - Půta, Pavel (2025)
The main objective of this master thesis is to conduct an internal IT audit engagement focused on IT operations, with a particular emphasis on the implementation of the JIRA system, and to perform qualitative research of the internal IT audit environment. The thesis is divided into two parts corresponding to these sub-goals. The first sub-goal is to execute an internal IT audit, including planning, execution, and final evaluation according to the corporate Group Audit Manual, with a special focus on a gap analysis aimed at the configuration and usage of the JIRA system. The second sub-goal is to conduct qualitative research using observation and semi-structured interviews. The outcomes of the thesis include a set of specific recommendations for improving the configuration and management of the JIRA system, such as workflow optimization and clearer user role definitions, as well as broader suggestions to enhance the efficiency of the internal IT audit process.